2016
DOI: 10.1007/s00220-016-2743-3
|View full text |Cite
|
Sign up to set email alerts
|

Bigeodesics in First-Passage Percolation

Abstract: In first-passage percolation, we place i.i.d. continuous weights at the edges of Z 2 and consider the weighted graph metric. A distance-minimizing path between points x and y is called a geodesic, and a bigeodesic is a doubly-infinite path whose segments are geodesics. It is a famous conjecture that almost surely, there are no bigeodesics. In the '90s, Licea-Newman showed that, under a curvature assumption on the "asymptotic shape," all infinite geodesics have an asymptotic direction, and there is a full measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…Tightly connected to the thermodynamic limit results in [GRASY15] are results on the limits of ratios of partition functions. Logarithms of these limiting ratios are polymer counterparts of Busemann functions that compare actions of infinite geodesics to each other in zero temperature models such as first passage percolation (FPP), last passage percolation, or zero-viscosity Burgers equation, see [HN01], [CP12], [BCK14], [Bak16], [GRAS16], [GRS15], [DH14], [DH17] and [AHD15], which is a recent survey on FPP. In [GRAS16] and [RSY16] a variational approach to ratios of partition functions is described.…”
Section: Directed Polymersmentioning
confidence: 99%
“…Tightly connected to the thermodynamic limit results in [GRASY15] are results on the limits of ratios of partition functions. Logarithms of these limiting ratios are polymer counterparts of Busemann functions that compare actions of infinite geodesics to each other in zero temperature models such as first passage percolation (FPP), last passage percolation, or zero-viscosity Burgers equation, see [HN01], [CP12], [BCK14], [Bak16], [GRAS16], [GRS15], [DH14], [DH17] and [AHD15], which is a recent survey on FPP. In [GRAS16] and [RSY16] a variational approach to ratios of partition functions is described.…”
Section: Directed Polymersmentioning
confidence: 99%
“…In the context of finite geodesics, has proved an upper bound on this failure probability of the form rc for some positive c>0, and there seems to be promise in these techniques to obtain a sharper form of the result. Hoffman initiated very fruitful progress on infinite geodesics in first passage percolation by using Busemann functions, with significant geometric information emerging in . Busemann functions have also been studied in non‐integrable last passage percolation contexts: see .…”
Section: Introductionmentioning
confidence: 99%
“…Recall that Licea and Newman showed that for "typical" directions θ -i.e., all θ in some set D Ď r0, 2πq -there is a.s. a unique θ-directed geodesic. We will describe work from [7] which extends these uniqueness statements using Busemann function techniques. In keeping with the above discussion, these results give not uniqueness of geodesics having some single direction θ, but rather uniqueness of geodesics directed within sectors (as produced by Theorem 7.2).…”
Section: Busemann Subsequential Limits and General Directedness Statementioning
confidence: 99%